Perceived parental affectionless control is associated with high neuroticism - Takahashi, Nana (Neuropsychiatr Dis Treat, 2017)
OBJECTIVE: Depressed patients are prone to perceive that they were exposed to affectionless control by parents. Meanwhile, high neuroticism is a well-established risk factor for developing depression. Therefore, this study examined whether perceived parental affectionless control is associated with high neuroticism. METHODS: The subjects were 664 healthy Japanese volunteers. Perceived parental care and protection were assessed by the Parental Bonding Instrument. Parental rearing was categorized into either optimal parenting (high care/low protection) or three dysfunctional parenting styles including affectionless control (low care/high protection). Neuroticism was evaluated by the NEO Personality Inventory-Revised. RESULTS: The subjects with paternal affectionless control had higher neuroticism scores than those with paternal optimal parenting. Similar tendency was observed in maternal rearing. Neuroticism scores increased in a stepwise manner with respect to the increase in the number of parents with affectionless control. CONCLUSION: The present study shows that perceived parental affectionless control is associated with high neuroticism, suggesting that this parental style increases neuroticism in recipients.